Composição e estimativa da abundância das principais espécies de Sciaenidae (Teleostei: Perciformes) em uma região estuarina do Norte do brasil - Cardoso, Camila de Nazaré Araújo (2014)
The present study shows the composition and time-space distribution of the main Sciaenidae species that occur in the Taperaçu estuary (Bragança, Pará). At a commercial level this is an important fish taxon specially to the bragantine region. Data were obtained in bimonthly samples in 24 hours from March, 2010 to July, 2011. Bottom trawn nets (25 mm mesh) and gill nets (meshes of 20 mm, 30 mm, 40 mm and 50 mm). The main species were caught at the young stages of genus Cynoscion, Macrodon, Micropogonias, Stellifer and Umbrina. The sampling representative numbers of each species was decisive to determine which genus will be investigated S. microps was the only specie with alometric positive growth; M. ancylodon was the most abundant (31.78%) and S. rastrifer shows significant differences between months. All results denote an ecological importance of the Taperaçu estuary to the Pará State saltmarsh zone.